Hardware-software co-simulation for medical X-ray control units - Kleinert, Bruno; Reza Rahimi, Gholam; Reichenbach, Marc; Fey, Dietmar (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2015)
In this paper we present our solution to master the complex- ity of product adaption cycles of a medical X-ray control unit. We present the real hardware and software platform and our mapping of it to a virtual X-ray control unit, im- plemented as our hardware-software co-simulation. To re- duce complexity for hardware developers, we developed our own XML-based abstract system description language which is mapped onto instantiations of parameterizable SystemC template modules. We verified the correctness of our virtual X-ray control unit by co-simulating unmodified software to hardware components, which we implemented in our system description language from the specification of the real sys- tem. Due to reduced complexity of our virtual X-ray control unit, it can be used as a time and cost saving test platform for future hardware and software adaption cycles.
Keywords: hardware-software co-simulation; virtual machines; qemu; systemc